Artemisinin-resistant malaria in Africa demands urgent action - Dhorda, M; Kaneko, A; Komatsu, R; Kc, A; Mshamu, S; Gesase, S; Kapologwe, N; Assefa, A; Opigo, J; Adoke, Y; Ebong, C; Karema, C; et al. (American Association for the Advancement of Science, 2024)
Artemisinin derivatives are the cornerstone of current antimalarial treatment, both for severe malaria (injectable artesunate) and uncomplicated malaria [artemisinin combination therapy (ACT)]. Although a large but poorly defined proportion of malaria infections remains undiagnosed, about 249 million uncomplicated cases were estimated worldwide in 2022, of which roughly 65% were treated with ACTs. Of these cases, 233 million (94%) occurred in Africa (1), where >70% of uncomplicated falciparum malaria cases are now treated with the ACT artemether-lumefantrine (AL). Unfortunately, artemisinin resistance (ART-R) has emerged in multiple locations in Africa, compromising the efficacy of ACTs. In the past, the spread of antimalarial resistance resulted in millions of avoidable deaths. Without radical action, this history will repeat itself. Success in containing ART-R in the Greater Mekong Subregion in Asia, where ART-R was first reported in 2008, suggests that a multipronged approach is needed in East Africa to reduce and interrupt malaria transmission permanently.